Identification of Badung Government Center (PUSPEM) as a Leading Family Tourism Attraction in Bali - Agung Bagus Widiantara, I Gusti; Wirya, I Made Suwitra; Susila, I Made Gede Darma (Akademi Komunitas MAPINDO, 2024)
The people of Badung Regency today have activities that are starting to be dense like people in other big cities. Almost every day, people in this city do activities outside the home by leaving other family members behind throughout the day. This condition causes a sense of boredom and on weekends requires a place to spend free time with family. In Badung Regency, one of the activities in this leisure time is carried out at the Badung Government Center which is located in the middle of this district, namely in Sempidi Village. Locations like this are very important to identify because they are very beneficial to the health of residents, both physically and mentally, with their family members. The data in this study were collected by methods: literature study, documentation, and observation. The research was conducted by qualitative descriptive data analysis method, by observing the 4A variables in the Badung Puspem as a family tourism attraction in Badung Regency, consisting of: Attraction, Amenities, Accessibility and Additional Services). The existence of the Badung Puspem in addition to being an office center to provide maximum service to the community can also function as a family tourism attraction in Badung Regency. Strengthened by the existence of the 4A element (Attraction, Amenity, Accessibility, and Ancilliary) with the support of various parties, starting from the Badung Regency government with the implementation of various policies, the private sector and the community, who are always loyal to take their time while helping to maintain the beauty, order and sanctity of this family tourist location.